2008
DOI: 10.1111/j.1525-142x.2008.00237.x
|View full text |Cite
|
Sign up to set email alerts
|

AINTEGUMENTA homolog expression in Gnetum (gymnosperms) and implications for the evolution of ovulate axes in seed plants

Abstract: SUMMARY The expression of GpANTL1, a homolog of AINTEGUMENTA (ANT) found in the gymnosperm Gnetum parvifolium, was analyzed by RT‐PCR and in situ hybridization. GpANTL1 was expressed in the leaf primordia, root tips, and young ovules. In the ovulate axis, expression was detected as four distinct rings around the outer, middle, and inner envelope primordia as well as around the nucellar tip. This pattern of expression is similar to that of ANT in Arabidopsis thaliana. A comparison of the expression of GpA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 51 publications
4
15
0
Order By: Relevance
“…3A). As observed by Floyd and Bowman (2007) and Yamada et al (2008) we additionally resolved within the eu-ANT lineage a clade including Arabidopsis ANT (the putative clade of ANT orthologs corresponding to the ''A'' clade of Floyd and Bowman, 2007 and the ''ANT (sensu stricto)'' clade of Yamada et al, 2008) and a clade of proteins most closely related to Arabidopsis BABY BOOM (BBM, the ''B'' clade of Floyd and Bowman (2007) and the ''BBM/PLT'' clade of Yamada et al (2008)) with significant bootstrap support (Fig. 3A).…”
Section: Ant and Bel1 Ortholog Identificationsupporting
confidence: 71%
“…3A). As observed by Floyd and Bowman (2007) and Yamada et al (2008) we additionally resolved within the eu-ANT lineage a clade including Arabidopsis ANT (the putative clade of ANT orthologs corresponding to the ''A'' clade of Floyd and Bowman, 2007 and the ''ANT (sensu stricto)'' clade of Yamada et al, 2008) and a clade of proteins most closely related to Arabidopsis BABY BOOM (BBM, the ''B'' clade of Floyd and Bowman (2007) and the ''BBM/PLT'' clade of Yamada et al (2008)) with significant bootstrap support (Fig. 3A).…”
Section: Ant and Bel1 Ortholog Identificationsupporting
confidence: 71%
“…This suggests that CrANT has an important role in sexual reproduction and that AthBBM might have evolved from an ancestral AIL gene such as CrANT . A single euANT gene has been reported for both Gnetum parvifolium and Pinus taeda (gymnosperms) and their expression pattern in young primordia indicate that they might have an important role in lateral organ size control as well as in the development of the ovule (Shigyo and Ito, 2004; Yamada et al, 2008), very similar to what has been reported for AthANT (Klucher et al, 1996; Mizukami and Fischer, 2000).…”
Section: Introductionsupporting
confidence: 72%
“…Meanwhile, because of the position of the single M. caldariorum and K. nitens sequences and the presence of the euANT1 motif in the first AP2 domain in these genes, we decided to name these two sequences as preANT (Figure 1, marked with purple). Within the land plant ANT clade two highly supported clades are recovered; the basalANT (98%) (Figure 1, cyan bar) and euANT (71%) (Figure 1, orange bar) clades that were reported in previous phylogenies of ANT genes (Kim et al, 2006; Floyd and Bowman, 2007; Yamada et al, 2008).…”
Section: Resultsmentioning
confidence: 60%
“…, 2003), it remains to be determined whether expression patterns of other polarity genes are similarly conserved in flowering plants. Likewise, few data exist about the distribution and expression of polarity genes outside of angiosperms, although ANT has been detected in gymnosperm integuments (Shigyo & Ito, 2004; Yamada et al. , 2008).…”
Section: Implications For Understanding Patterns Of Seed Plant Ementioning
confidence: 99%